Sentiment analysis: the case of twitch chat - Mining user feedback from livestream chats - Reis, Jaime Mendes Gouveia Batalha (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management